Peripheral Female Genital Arousal as Assessed by Thermography Following Topical Genital Application of Alprostadil vs Placebo Arousal Gel: A Proof-of-Principle Study Without Visual Sexual Stimulation - Sue W. Goldstein, BA, CCRC, IF; Joshua R. Gonzalez, MD; Catherine Gagnon, NP-C; Irwin Goldstein, MD (Sexual Medicine, 2016)
Introduction: Female sexual arousal disorder is a pathophysiologic state characterized clinically by persistent or recurrent inability to attain or maintain an adequate lubrication-swelling response of sexual excitement until completion of sexual activity. Prior clinical experience with alprostadil products for men with erectile dysfunction supports its use in women with female sexual arousal disorder. Aim: To compare the effect of topical alprostadil with over-the-counter (OTC) lubricant on female genital arousal in the absence of visual sexual stimuli. Methods: Healthy premenopausal women without sexual dysfunction were recruited from the community to participate in the study. Of 17 women who consented, 10 were enrolled and completed the trial. The mean age of subjects was 32 years (range = 27–43). Study drug or placebo was applied topically to the genitals. Continuous temperature monitoring was performed. Participants completed questionnaires assessing genital sensation, effect, intensity, and duration. Main Outcome Measures: Change in temperature from baseline in vestibule, clitoris and vulva. Results: In all 10 subjects, topical alprostadil induced a statistically significant increase in temperature of the vestibule, clitoris, and vulva compared with the OTC lubricant. The most rapid difference in genital temperature between placebo and alprostadil was seen on the vulva, which demonstrated a significant difference at approximately 9 minutes. There was a significant difference in temperature seen for the vestibule and clitoris at 11 and 19 minutes, respectively. Sixty percent of women reported being aware or conscious of genital sensations with topical alprostadil, but not with OTC lubricant. Discordance was noted in 30% of subjects who reported being aware or conscious of genital sensations with the two treatments and 10% who reported not being aware or conscious of genital sensations with either treatment. Conclusion: Topical alprostadil administered to healthy premenopausal women induced statistically significant, sustained increases in genital temperatures of the vestibule, clitoris, and vulva within 20 minutes compared with OTC lubricant.